B-Doped PdRu nanopillar assemblies for enhanced formic acid oxidation electrocatalysis. Issue 37 (18th September 2020) - Liu, Songliang; Wang, Ziqiang; Zhang, Hugang; Yin, Shuli; Xu, You; Li, Xiaonian; Wang, Liang; Wang, Hongjing
Abstract : B-Doped PdRu nanopillar assemblies have been synthesized for the formic acid oxidation reaction with enhanced catalytic performance. Abstract : Adjusting the morphology and composition of Pd-based materials is a promising strategy to improve their performance for the electrocatalytic formic acid oxidation reaction (FAOR). In this work, we report the preparation of B-doped PdRu nanopillar assemblies (B-PdRu NPAs) by a two-step method using NaBH4 as the boron dopant. On combining the hyper-branched structure and the multi-component synergistic effect, B-PdRu NPAs achieve a high mass activity of 1.09 mA μg −1 Pd for the FAOR and retain 73.19% of the initial activity after 500 cycles, which is superior to undoped counterparts. The proposed synthesis strategy provides a simple method for the synthesis of metal–nonmetal nanomaterials with desired composition and design structure for electrocatalytic fields.